Stadium's wireless control system using Global System for Mobile Communication (GSM) and Arduino controller / Ahmad Syakirin Ismail @ Rosdi - Ismail @ Rosdi, Ahmad Syakirin (2014)
This report presents a project of control system for stadium which used Arduino UNO and Arduino Mega as the controller and GSM as the wireless control device. Servo motor used in this project is to move some of the parts like door lock, roof and etc. This project use Arduino IDE software which is designed for the Arduino controller. All operation systems are controlled through message and all orders were written by programming. Analysis to test the effectiveness of this system against range between transmitter (handset) and receiver (GSM and Arduino) has been done. Five different ranges were used which are 2 meter, 5 meter, 10 meter, 50 meter, 100 meter and 1km and were tested at three different places which have different signal strength. The effectiveness of this system can be seen from the time taken by the system to operate when it has been given orders. Stop watch was used to record the time. From the analysis, this system does not affected by distance but it is strongly dependent on signal strength.